Oxidative Stress in Parasites - Ankri, Serge (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Parasitic infections pose a significant public health challenge, particularly in developing countries, and can lead to long-term illness, disability, and even death. This reprint focuses on parasitic diseases and how parasites respond to the oxidative and nitrosative stress generated by the host's immune system. The articles in this Special Issue cover various aspects of this topic, including the localization of parasites within the host, the impact of nutrition and drugs, and the role of the host's immune defense cells in the parasitic response to oxidative and nitrosative stress. Understanding the mechanisms underlying parasitic diseases is crucial for developing innovative treatments that can target parasites' defense against oxidative stress. This Special Issue serves as a valuable resource for researchers, students, and physicians interested in parasitic infections.